The role of digital news in shaping inflation expectations: Evidence from an emerging economy (Colombia, 2009-2018) - Anzoátegui, Juan Camilo (2026)
The aim of this paper is to investigate the effects of digital mass media on the formation of inflation expectations. In particular, this paper assesses the effects of digital news on inflation on disagreements in consumer inflation expectations. For this, the Colombian economy for the period 2009-2018 is used as a case study. The methodology used consists of evaluating the effects of the news on inflation provided by five representative digital newspapers on the disagreements. By means of econometric regressions, and using the GMM method, the largest volume of news on inflation is found, as well as news on increases and with a negative tone on inflation, have the ability to reduce discrepancies between agents